Decreasing the Polarization Resistance of BaCo0.7Fe0.2Nb0.1O3–δ Cathodes by Infiltration of Ce0.8Y0.2O2–δ. Issue 5 (1st September 2016) - Wang, T. H.; Sun, C. C.; Zhen, F.; Song, W. J.; Li, R.; Zhen, Q.
Abstract: Ce0.8 Y0.2 O2– δ (YDC) was infiltrated into a BaCo0.7 Fe0.2 Nb0.1 O3– δ (BCFN) cathode of intermediate temperature sold oxide full cells (IT‐SOFCs) in order to decrease its cathodic polarization resistance. BCFN and YDC infiltrated BCFN electrodes were fabricated on dense Ce0.8 Gd0.2 O2– δ (GDC) thin pellets to form symmetrical cells. The electrochemical impedance spectra of the symmetrical cells were investigated in this present study. Firstly, the thickness of BCFN electrodes was optimized, and controlled at 30 µm for further study. The effects of infiltrated YDC amount and firing temperature on electrode polarization resistance were studied. The symmetrical cells infiltrated with 30 μL YDC solution and fired at 900 °C exhibited the lowest electrode polarization resistance in all samples. It was suggested that infiltration of YDC resulted in more active sites and prolonged TPBs in electrodes, improving the surface oxygen exchange, and finally improved the electrode performance.